Ethnobotany of Amorphophallus paeoniifolius: Morphology, folk classification, and habitat in area around Ciremai Mountain, Cimanuk Watershed Region, West Java, Indonesia - ASEP ZAINAL MUTAQIN; DENNY KURNIADIE; JOHAN ISKANDAR; MOHAMAD NURZAMAN; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mutaqin AZ, Kurniadie D, Iskandar J, Nurzaman M, Partasasmita R. 2020. Ethnobotany of Amorphophallus paeoniifolius: Morphology, folk classification, and habitat in area around Ciremai Mountain, Cimanuk Watershed Region, West Java, Indonesia. Biodiversitas 21: 3898-3909.  Plants that grow in the world have a diversity of names, characters, and growing environments. Likewise, plants that grow around Ciremai Mountain, including the Cimanuk Watershed, are very diverse in species and habitats. One species of plant in this region is Amorphophallus paeoniifolius (Dennst.) Nicolson. This plant is closely related to people's lives. This plant is a species of the tuber that has the potential to be used for various purposes. This study aims to determine the knowledge of the people about the ethnobotany of A. paeoniifolius especially the morphology, folk classification, and habitat with case studies in several villages in Cikijing Sub-district, Majalengka District which is ecologically located in the Ciremai Mountain neighborhood and, based on geography, is included in the Cimanuk Watershed. The qualitative method is used in this research. The data were collected through observation and semi-structured interviews or deep interviews with competent communities by focusing on their diversity. Data were analyzed by cross-checking, summarizing, and synthesizing and were narrated descriptively through an emic and ethical approach. The results showed that the people in the Ciremai Mountain neighborhood, namely Cipulus Village, Cilancang Village, Jagasari Village, and Sindangpanji Village, Cikijing Sub-district, Majalengka District knew names, morphology, and folk classification of A. paeoniifolius. This plant is popularly known as suweg in local name. People's knowledge related to morphology (leaves, tubers, roots, and flowers) in these areas is generally not much different. Related to folk classification, people generally say that suweg has variant based on the color of the tubers and sunlight exposure to the place of growth. The intended variant is suweg with reddish-white and yellowish-white of the tuber flesh’s color. Another classification is the suweg variant which grows in the hieum (shading area) and negrak (open area). Concerning hábitat, the people informed that the suweg grows in the garden and homegarden (specifically in the Sindangpanji village, the people said that besides growing in both types of land, the suweg also grows on the edge of rice fields and ponds). Besides, suweg also grows in hot and cold (tiis) conditions; from the beginning of the rainy season to the beginning of the dry season, which is marked by yellowing and falling of leaves; in various soil conditions (such as red, black, brown or sandy soil); and with various species of plants (except with eurih and areuy,in which the growth of the plant is not optimum).